2021
DOI: 10.1002/ecs2.3436
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the 2016 Yellowstone River fish kill and proliferative kidney disease in wild fish populations

Abstract: Proliferative kidney disease (PKD) is an emerging disease that recently resulted in a large mortality event of salmonids in the Yellowstone River (Montana, USA). Total PKD fish mortalities in the Yellowstone River were estimated in the tens of thousands, which resulted in a multi-week river closure and an estimated economic loss of US$500,000. This event shocked scientists, managers, and the public, as this was the first occurrence of the disease in the Yellowstone River, the only reported occurrence of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Naldoni et al (2019) found indications of parasite spore production in whitefish, but due to co-infection of a sphaerosporid species, they could not confirm that European whitefish is a true host for T. bryosalmonae . The parasite was also detected in mountain whitefish (Prosopium williamsoni) in a severe outbreak with high mortalities in Yellowstone, Montana, USA, in 2016 (Hutchins et al, 2021;Opitz, 2017;Opitz & Rhoten, 2016). Hutchins et al (2021) detected T. bryosalmonae presence in a broad host range in a wide distribution area of Montana, but mountain whitefish have the highest prevalence (50%) among the species.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Naldoni et al (2019) found indications of parasite spore production in whitefish, but due to co-infection of a sphaerosporid species, they could not confirm that European whitefish is a true host for T. bryosalmonae . The parasite was also detected in mountain whitefish (Prosopium williamsoni) in a severe outbreak with high mortalities in Yellowstone, Montana, USA, in 2016 (Hutchins et al, 2021;Opitz, 2017;Opitz & Rhoten, 2016). Hutchins et al (2021) detected T. bryosalmonae presence in a broad host range in a wide distribution area of Montana, but mountain whitefish have the highest prevalence (50%) among the species.…”
Section: Discussionmentioning
confidence: 98%
“…The parasite was also detected in mountain whitefish (Prosopium williamsoni) in a severe outbreak with high mortalities in Yellowstone, Montana, USA, in 2016 (Hutchins et al, 2021;Opitz, 2017;Opitz & Rhoten, 2016). Hutchins et al (2021) detected T. bryosalmonae presence in a broad host range in a wide distribution area of Montana, but mountain whitefish have the highest prevalence (50%) among the species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, their size may enable them to stay in areas with higher water flow rates as has been reported for larger fish (Hockley et al, 2014). In this context, it has been suggested that often lower flow regimes are associated with the environmental parameters linked with an increased abundance of T. bryosalmonae malacospore release from the bryozoan host (Hutchins et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it has been suggested that often lower flow regimes are associated with the environmental parameters linked with an increased abundance of T . bryosalmonae malacospore release from the bryozoan host (Hutchins et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%